Lexical comparison in Hayu: a lexicostatistical analysis - Rai, Tara Mani (Gipan, 2019)
This article presents the lexicostatistical analysis of Hayu language based on 210 wordlist. There appear different ranges of lexical and phonetic similarities across the five different survey points. Being based on the Mudhajor, the core area of Hayu, exhibits a significant degree of lexical similarity with other points, i.e. Aadmara, Kodre, Wadi and Balingkhola. Such similarity percentages clearly indicate that Hayu spoken in five different points are mutually intelligible to each other. The lexicostatistical data, therefore, show that there is not much lexical variations across the villages where Hayu is spoken.